(untitled) (The Lumbini Journal of Business and Economics, 2025)
Purpose: The main purpose of the study is to investigate the effect of non-performing loan ratio (NPLR), loan to deposit ratio (LDR), interest income to loan and advance ratio (ILAR), and capital adequacy ratio (CAR) on the return on assets (ROA) of commercial banks in Nepal. Methods: The balance panel data of eighteen commercial banks based on data availability with 180 observations covering 2013/14 to 2022/23 have been used for analysis. Descriptive methods used to summarize data, correlation method used to examine relationships between variables, and the random effect regression model used to predict outcomes and assesses variable influence. Results: The results show that the NPLR and LDR have a negative and significant effect on the financial performance (ROA) of commercial banks in Nepal. ILAR has a positive and insignificant effect and CAR has a positive and significant effect on the financial performance (ROA) of commercial banks in Nepal. Conclusion: Banks should focus on reducing non-performing loan ratio, loan supply to the productive sector, and maintaining an optimal level of capital adequacy ratio to improve their financial performance.